Pengembangan program pendidikan kompetensi sosial pengasuh pesantren tingkat SMP - Arifin, Zainurroyyan; Al Katani, Abdul Hayyie; Syafri, Ulil Amri (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This study aims to develop an Islamic social competence education program for junior high school Islamic boarding school caregivers. The background of this research is the importance of caregivers' roles as mentors for students in character development, yet many of them lack adequate social competence. The study used a Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The results indicate that most Islamic boarding school caregivers have not received social training based on Islamic values and require a systematic program. The program developed encompasses the values of tazkiyatun nafs (self-control), sincerity, adab al-mu'asyarah (concerning good and forbidding evil), patience, gratitude, humility (tawadhu'), love of knowledge, asceticism (zuhud), Islamic brotherhood (ukhuwah Islamiyah), and morally-based social leadership. Expert validation showed a feasibility level of 81.6% (highly feasible). The implementation results indicate that this program can help improve the social competence of caregivers in carrying out their social roles and fostering students in the Islamic boarding school environment. Keywords: social competence, Islamic boarding school caregivers, Islamic education, program development. Abstrak Penelitian ini bertujuan untuk mengembangkan program pendidikan kompetensi sosial Islami bagi pengasuh pesantren tingkat SMP. Latar belakang penelitian ini adalah pentingnya peran pengasuh sebagai figur pembimbing santri dalam pembentukan karakter, tetapi banyak di antara mereka belum memiliki kompetensi sosial yang memadai. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang mencakup lima tahap: analisis, desain, pengembangan, implementasi, dan evaluasi. Hasil penelitian menunjukkan bahwa sebagian besar pengasuh pesantren belum memperoleh pelatihan sosial berbasis nilai-nilai Islam dan membutuhkan program yang sistematis. Program yang dikembangkan meliputi nilai-nilai tazkiyatun nafs, keikhlasan, adab al-mu’asyarah, amar ma’ruf nahi munkar, sabar, syukur, tawadhu’, cinta ilmu, zuhud, ukhuwah Islamiyah, dan kepemimpinan sosial berbasis akhlak. Validasi ahli menunjukkan tingkat kelayakan 81,6% (kategori sangat layak). Hasil implementasi menunjukkan program ini dapat membantu meningkatkan kompetensi sosial pengasuh dalam menjalankan peran sosial dan pembinaan santri di lingkungan pesantren.